PENGARUH KUALITAS PRODUK, BRAND AMBASSADOR DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN NATURE REPUBLIC - Rohmatul Ummat; Kristina Anindita Hayuningtias (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Product Quality, Brand Ambassador and Price Perception on Purchase Decisions. This study uses a sampling method using a purposive sampling method with the criteria of having purchased a Nature Republic product at least once. The results of this study indicate that jointly Product Quality, Brand Ambassador, and Price Perception have an effect on Purchase Decisions. However, partially product quality and price perception have a significant positive effect on purchasing decisions. Meanwhile, Brand Ambassador has no significant effect on Purchase Decision. The three independent variables, that the quality product has values is dominate than the Price Perception and Brand Ambassador.